A distinguishing method of open-circuit IGBT of three-level NPC inverter - QIU Shiguang; LI Mei (Gong-kuang zidonghua, 2014)
For problem of large calculated amount of existing distinguishing method of open-circuit IGBT of three-level NPC inverter, all kinds of open-circuit states of IGBT were simulated, and the causes of bus neutral-point voltage deviation were analyzed, then a simple method to distinguish the open-circuit IGBT was proposed. The method achieves distinguishing of open-circuit IGBT by detecting bus neutral-point voltage and three-phase output voltage of inverter, which needs no extra hardware. The simulation results verify effectiveness of the method.